Penerapan Sistem e-Procurement Dalam Tata Kelola Pengadaan Barang dan Jasa (Studi Kasus : Badan Layanan Pengadaan Secara Elektronik (LPSE) Kota Denpasar) - Pramasari, Kadek Lori (CITIZEN CHARTER, 2014)
ABSTRACT This study thoroughly discussed about the mechanism of procurement of goods and services in the Denpasar Government, from the collection of initial bidders until the announcement of the winner of the auction at the City of Denpasar. This study also did not escape discusses transparency and accountability of the implementation of the electronic procurement system in the City of Denpasar. Keywords: Application of Electronic Systems Procurement, e-Procurement Mechanism